2018
DOI: 10.1038/s41422-018-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage triggers tubular endoplasmic reticulum extension to promote apoptosis by facilitating ER-mitochondria signaling

Abstract: The endoplasmic reticulum (ER) is composed of the nuclear envelope, perinuclear sheets and a peripheral tubular network. The peripheral ER and mitochondria form tight contacts at specific subdomains, which coordinate the functions of the two organelles and are required for multiple cellular processes such as Ca2+ transfer and apoptosis. However, it is largely unknown how ER morphology and ER-mitochondria signaling are dynamically regulated under different physiological or pathological conditions such as DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 88 publications
3
71
0
Order By: Relevance
“…This view is consistent with recent studies that connected using unbiased approaches the pathways involved in maintenance of genome integrity and proteostasis, showing that dysregulation of the DDR resulted in protein aggregation and autophagy induction 30,31 . Moreover, previous work demonstrated that the function and structure of the ER is drastically affected by DNA damaging agents used in chemotherapy 32,33 . Other recent reports suggested that chronic ER stress suppresses DNA repair and sensitizes cancer cells to ionizing radiation and chemotherapy [34][35][36][37] , in addition to enhancing oxidative damage to the DNA 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This view is consistent with recent studies that connected using unbiased approaches the pathways involved in maintenance of genome integrity and proteostasis, showing that dysregulation of the DDR resulted in protein aggregation and autophagy induction 30,31 . Moreover, previous work demonstrated that the function and structure of the ER is drastically affected by DNA damaging agents used in chemotherapy 32,33 . Other recent reports suggested that chronic ER stress suppresses DNA repair and sensitizes cancer cells to ionizing radiation and chemotherapy [34][35][36][37] , in addition to enhancing oxidative damage to the DNA 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggested that mitochondrial-dependent apoptosis is typically initiated by DNA damage which further modulates cellular redox status associated with the cell death mechanism. 35,36 Histone H2AX phosphorylated on serine 139 (γ-H2AX), one of the hallmarks of DNA damage and DNA double-strand breaks (DSB), is modulated through iROS. Thus, to assess the role of CeO 2 in the induction of DNA damage, immunofluorescence study was carried out to detect the phosphorylation of γ-H2AX underlying the foci formation in the nucleus.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, growth arrest may result from ER stress-induced regulation of G2/M transition through the eIF2α signaling pathway [41]. This finds confirmation in observations on DNA damage-mediated tubular endoplasmic reticulum extension, promoting apoptosis by the facilitation of ER-mitochondria signaling [42]. Furthermore, the elevated phosphorylation status of eIF2α was accompanied by inhibition of CHOP, a factor activating transcription of murine double minute 2 that targets p53 for degradation and is required for neuroprotection [43].…”
Section: Discussionmentioning
confidence: 75%